Bruno Zevi in 1950s Spain: a Storia dell'architettura imbued with the future - Garnica González-Bárcena, Julio (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
In December 1950 the Italian architect Bruno Zevi published the first edition of his book “Storia de l'architettura moderna”, written as a continuation of, and largely a contrast to, the other “histories” of modern architecture that had been published up to that time. The release of the book, which incited immediate interest from architects, critics and architecture historians, coincided with Zevi’s emergence as a public figure in 1950s Spain. In September 1949, his first article in Spanish was published in the informational bulletin of the General Directorate of Architecture: it was the text of his lecture “Organic architecture in the face of its critics”. A year later, in May 1950, Bruno Zevi participated in a lecture series organized by the Architects’ Association in Barcelona, where he made two contributions focused on the crisis of architectural rationalism and the situation of Italian architecture at the time. It was then that, through his local colleagues, he “discovered” the work of Gaudí, whose architecture – a full-color image of a bench from Park Güell – ended up on the cover of his decisive “Storia de l'architettura moderna”. With the operational recovery of a figure then virtually unknown in the panorama of fin-de-siecle Europe, Zevi established one of the soundest precedents for an “organic architecture” destined to overcome the limits of early modernity.
Keywords: Zevi; Organic architecture; History; Gaudí; 1950